(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides information on the gas industry, gas transportation to consumers, the structure of the gas network of the Republic of Uzbekistan, as well as information on the environmental control of the gas network. In addition, measures are given to ensure environmental safety in the gas supply system.